Pemanfaatan Lubuk Larangan sebagai Sumber Belajar Kontekstual pada Pembelajaran IPA di Sekolah Dasar Kabupaten Merangin - Shobrina Fitri; Egi Agustandi; Muhammad Ali Imron; Diva Apri Mulya; Muhamat Soprian (PT. Penerbit Tiga Mutiara, 2026)
Science learning in elementary schools is still predominantly based on textbooks, resulting in the underutilization of the local environment as a contextual learning resource. Consequently, students have not yet gained meaningful learning experiences that connect scientific concepts with real-world phenomena in their surrounding environment. This study aims to analyze the potential of Lubuk Larangan in Merangin Regency as a contextual learning resource, examine the integration of ecosystem concepts and local wisdom into science learning, and explain its contribution to students' conceptual understanding, science process skills, and environmental awareness. The findings indicate that Lubuk Larangan functions as a natural laboratory that supports contextual learning through direct observation of river ecosystems, thereby enhancing scientific thinking skills, learning motivation, active participation, and appreciation of local culture. Its implementation requires the support of instructional materials, collaboration among stakeholders, and school policies to ensure sustainability. The novelty of this study lies in the development of a community-based natural laboratory perspective of Lubuk Larangan that integrates river ecology, ethnoscience, conservation practices, science learning, and character education.